Leadership and Small Business The Power of Stories - Hutchinson, Karise (Springer International Publishing, 2018)
"The story in this book is compelling- a must read for students, entrepreneurs and practitioners alike. [Invest NI] supported Lead2Grow because we know the difference this programme can make to the small business taking part and ultimately the positive impact their growth can have on the economy." - - Grainne McCurry, Head of Leadership and Management, Invest Northern Ireland "This book exemplifies the significance of academic research in the real and challenging world of small business." - Professor Cary Cooper, President British Academy of Management and Professor Nic Beech, Chair British Academy of Management This innovative book combines theoretical and practical perspectives with the power of storytelling to present a new understanding of leadership as a concept and endeavour in the small business organisation. With the assertion that leadership capability is a key function of small firm survival and growth, it underlines the importance of addressing the phenomenon within small business. Employing storytelling as a fresh alternative to a traditional case study approach, the narrative of leading with purpose in real time is captured alongside relevant and current academic debate. In building upon the Harvard model of purpose driven leadership, the author offers a new definition and discussion of leadership that connects theory to real impact, based on research carried out with UK small business organisations. The overall aim of the book is to provoke interest in small business leadership and generate new knowledge of leading with purpose.